Ashab al-Kahf in the Writings of the Orientalist Johann Wolfgang von Goethe: A Semantic Study of the Intertextuality with Surah Al-Kahf: أصحاب الكهف في كتابات المستشرق يوهان فولفغانغ فون غوته: دراسة دلالية لألفاظ التناص مع سورة الكهف - Albshkar, Hajer; Ayad, Nahid; Alouzi, Khuloud; Masuwd, Mowafg; Abdulghani, Naser (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2024)
This study analyses how the poem "Ashab al-Kahf" in the writings of the orientalist Johann Wolfgang von Goethe connects with Surah Al-Kahf through intertextuality. The overlap of the poem with the story " Ashab al-Kahf" in the Quranic Surah highlighted the extent of Johann Wolfgang von Goethe's influence by the Quran and Islamic heritage. This research aimed to study and analyze some of the words used in the poem using an analytical and comparative approach to understand Johann Wolfgang von Goethe's understanding of the story, the significance of the chosen words, and the impact of intertextuality with the Quranic text on shaping the poem's meanings. The findings indicated that Johann Wolfgang von Goethe faithfully presented the events, characters, and the spatial context of the story. His chosen words highlight the strong link between the poem and the Quranic text which shows the author's deep engagement with the Quranic narrative.